전국 승가대학 예비승려들의 식행동과 음식기호도에 관한 연구 - 한수진(Su-Jin Han); 이심열(Sim-Yeol Lee) (Korean journal of community nutrition, 2017)
Objectives: This study was designed to find out factors that are needed to be improved for the Buddhist training environment of Sramanera Sramanerika monks, who have been newly adapted for their life style after becoming a monk, and to provide basic data for the development of the standard diet in Buddhist temples. Methods: A self-administered questionnaire was applied to 365 Sramanera Sramanerika monks at 11 Buddhist monk universities. The questionnaire was designed to investigate their dietary habits, dietary evaluation, satisfaction of food service, and food preferences. Results: The study population consisted of 52.6% men, and 47.4% women. The subjects who had a vegetarian diet before joining the Buddhist priesthood were 27.7% women, and 13.5% men (p<0.01). 42.2% of the total subjects felt that they are healthy now and 19.4% felt weak. The most difficulty of dieting adaptation as soon as entering the priesthood was the strict diet rules (42.9%). The subjects considered health or nutrition (40.0%) highly when having meals. 94.8% women, 84.1% men ate breakfast every day (p<0.001). Women (55.4%) frequently ate snacks more than men (26.6%) (p<0.001). The results of the dietary evaluation indicated that the intake of milk, soy milk or dairy products and beans or tofu received lower than 3 points and women had lower point result than men (p<0.001). Foods with higher preference were grilled mushrooms, grilled laver, miso stew, sweet and sour mushrooms, steamed tofu with seasoning. Conclusions: Women were more interested in their health than men but they also required to improve the nutritional eating habits. It appeared that the lower intake rates of the calcium containing food (milk and dairy), and proteins (beans and tofu) could result in nutritional imbalance. Therefore, it is necessary to offer food based on the standard menu plan with consideration given to their food preferences in order to maintain their health and desirable dietary habits.